2005
DOI: 10.1016/j.curtheres.2005.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isoflurane, sevoflurane, and desflurane on platelet function: A prospective, randomized, single-blind, in vivo study

Abstract: In this study of the effects of isoflurane, sevoflurane, and desflurane in patients undergoing minor surgery, clinically relevant antithrombotic effects were observed 15 minutes after intubation with all 3 drugs, although the effects in patients receiving sevoflurane were significantly greater compared with those in patients receiving isoflurane and desflurane. The antithrombotic effects of isoflurane and desflurane were not continued at 1 hour after surgery; however, the inhibitory effects of sevoflurane on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
(3 reference statements)
0
14
0
Order By: Relevance
“…Clinically relevant antithrombotic effects of 1 MAC isoflurane, sevoflurane and desflurane was observed 15 min after intubation, by using platelet function analyzer (PFA-100) during minor surgery. Also, no significant difference was reported in INR, PT, aPTT as well as Hct, Hb and platelet count, at various timings [7].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Clinically relevant antithrombotic effects of 1 MAC isoflurane, sevoflurane and desflurane was observed 15 min after intubation, by using platelet function analyzer (PFA-100) during minor surgery. Also, no significant difference was reported in INR, PT, aPTT as well as Hct, Hb and platelet count, at various timings [7].…”
Section: Discussionmentioning
confidence: 77%
“…Isoflurane, sevoflurane and desflurane anesthesia were reported to have relative clinical anticoagulant properties during minor surgical procedures [7]. Desflurane showed better postoperative hepatic function tests and INR results when compared with both isoflurane at equivalent doses [8] and total intravenous anesthesia (TIVA) with propofol-remifentanil [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, blood was collected for analysis of platelet function before administration of any anesthetic medication and performance of endoscopy, and there was at least a 14‐day recovery period before collection of the next blood sample. Additionally, the anesthetic protocol used in the related study (acepromazine, butorphanol, and isoflurane) has been shown to have no significant sustained effect on platelet function 36‐39 . However, the instruments used to assess platelet function in these studies were different than the instruments used in our study 36‐39 .…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, the anesthetic protocol used in the related study (acepromazine, butorphanol, and isoflurane) has been shown to have no significant sustained effect on platelet function 36‐39 . However, the instruments used to assess platelet function in these studies were different than the instruments used in our study 36‐39 . Finally, our study only used 1 thromboprophylactic agent.…”
Section: Discussionmentioning
confidence: 82%
“…The underlying mechanisms is thought to be through immediate inhibition of granulocyte-platelet aggregation by suppression of thromboxane A2 formation, inhibition of calcium mobilization in platelets and inhibition of platelet aggregation. [37,38,39] Significantly reduced platelet count detected in our study predominantly in CHC groups. Concurring with other studies which reported reduced platelet counts, due to platelet accumulation in liver during I/R.…”
Section: Discussionmentioning
confidence: 78%